BUDAYA KARAKTER DAN MORAL REMAJA MASA KINI MERUPAKAN STRATEGI TEPAT PENCEGAHAN KORUPSI - Rudy Budiatmaja (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2022)
The number of cases or phenomena that are rife lately such as corruption which causes our mentality as teenagers is very concerning, as if moral behavior and character education for teenagers are currently destroyed and can even be said to be almost non-existent, so the purpose of this research article is that we as the younger generation must activate and regenerate moral behavior with a strong character and not be tempted to corruption. Researchers use qualitative research materials as research methods where all literature is primary data from books, scientific journals and other researchers. The results of this research article are that young people who have high moral character must say no to things that lead to corruption so that it can be concluded that innovative thinking can provide new enthusiasm for moral behavior and character education for today's youth aware that the dangers of rampant corruption culture in Indonesia and strive to firmly reject corruption. The state are said to be sovereign and an advanced economy must be free from its dilapidated condition that tarnishes the good name of a nation if corruption is still number one in the country, thus we all must be able and work hard so that the image of the Indonesian nation is fragrant in the eyes of all nations in this world because The Indonesian nation stands on the One Godhead who has a spirit of trust not to commit violations, especially corruption and the Indonesian people should have morals and character.